2021
DOI: 10.21203/rs.3.rs-675301/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development, Disappearance, and Clinical Course of Melanosis Coli: Sex Differences in Progression of Severity

Abstract: Background Melanosis coli (MC) is an acquired colorectal disorder visualized as colonic mucosa pigmentation. Disease severity is confirmed based on MC depth, shape, and coloration, although the clinical course is not fully understood. This study sought to clarify characteristics of MC development and disappearance and to demonstrate its clinical course and severity. Contributors to progression of MC grade were also explored. Methods To investigate the patient and clinical features of developing and disappear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 11 Although both sexes are affected equally, a recent study revealed that there is a greater tendency for progression among male patients. 12 There is no documented relation between NAFLD and development of Melanosis coli . Instead, the sennosides are known for their mitochondrial protective effect and inhibition of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Although both sexes are affected equally, a recent study revealed that there is a greater tendency for progression among male patients. 12 There is no documented relation between NAFLD and development of Melanosis coli . Instead, the sennosides are known for their mitochondrial protective effect and inhibition of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 14 Dis-appearance of hyperpigmentation is commonly expected after 2 years. 12 But histological findings may persist for many years. 14 Our patient was advised to stop using herbal tea and to manage his constipation with a high-fiber diet.…”
Section: Discussionmentioning
confidence: 99%